Hepatic lipid metabolism and non-alcoholic fatty liver disease in aging. (5th November 2017) - Gong, Zhenwei; Tas, Emir; Yakar, Shoshana; Muzumdar, Radhika
Abstract: Aging is associated with dysregulation of glucose and lipid metabolism. Various factors that contribute to the dysregulation include both modifiable (e.g. obesity, insulin resistance) and non-modifiable risk factors (age-associated physiologic changes). Although there is no linear relationship between aging and prevalence of non-alcoholic fatty liver disease, current data strongly suggests that advanced age leads to more severe histological changes and poorer clinical outcomes. Hepatic lipid accumulation could lead to significant hepatic and systemic consequences including steatohepatitis, cirrhosis, impairment of systemic glucose metabolism and metabolic syndrome, thereby contributing to age-related diseases. Insulin, leptin and adiponectin are key regulators of the various physiologic processes that regulate hepatic lipid metabolism. Recent advances have expanded our understanding in this field, highlighting the role of novel mediators such as FGF 21, and mitochondria derived peptides. In this review, we will summarize the mediators of hepatic lipid metabolism and how they are altered in aging. Highlights: Aging increases the risk for non-alcoholic fatty liver disease (NAFLD) and associated comorbidities. Impaired fatty acid oxidation and increased de novo lipogenesis in the liver contribute to the age-associated increase in hepatic steatosis. Insulin resistance is the major cause of hepatic lipid accumulation and NAFLD. GH-IGF-1 axis, Leptin, Adiponectin and inflammation play critical roles in age-related NAFLD. FGF-21 and mitochondria-derived peptides are potential novel players in the regulation of hepatic lipid accumulation.